Environment-friendly dust suppressant for coal transportation and preparation method thereof
By adding functional components and modified sodium alginate to the dust inhibitor and carrying out chemical crosslinking reaction, the problem of poor water resistance of existing dust inhibitors is solved, and the water resistance and mechanical properties of the dust inhibitors are significantly improved.
Patent Information
- Application Number
- CN202510321814.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing dust suppressors have poor mechanical properties and poor water resistance, which will affect the dust suppression effect.
An environmentally friendly dust inhibitor for coal transportation is adopted, which includes functional components, modified sodium alginate, initiator, phytic acid and genipin, and the water resistance and mechanical properties of the dust inhibitor are improved through chemical crosslinking reactions.
The wind corrosion resistance, water resistance and mechanical properties of the dust inhibitor are improved, ensuring that dust suppression can still be effectively suppressed under rainwater erosion.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of railway transportation dust control, and more specifically, to an environmentally friendly dust suppressant for coal transportation and a preparation method thereof. Background Art
[0002] As an important industrial raw material and basic energy source, coal is mined and utilized on an increasingly large scale, driven by the rapid development of the coal industry and the continuous improvement of the mechanization level. However, a large amount of coal dust is generated during coal mining, processing, and transportation, which not only pollutes the environment, but also exposes miners to a high concentration of dust, seriously threatening their health and life safety. In order to prevent and control the hazards of coal dust, many dust suppression technologies and methods have been developed. Among them, chemical dust suppression technology has the advantages of good dust suppression effect and water conservation, and has attracted widespread attention from scholars. However, it has the disadvantage of easily causing secondary pollution.
[0003] With the development of economy and society, the demand for coal is increasing, and the demand for green, environmentally friendly and high-performance dust suppression technology is getting higher and higher. The existing environmentally friendly dust suppressants mainly use the network structure formed by the cross-linking of the polymer substances in their components to lock the coal powder particles, and after losing water, they form a solid shell with sufficient thickness and good seismic and compressive properties with the coal powder particles to achieve efficient dust suppression of coal during railway transportation. However, most of the polymer substances used in the preparation of environmentally friendly dust suppressants have general wind erosion resistance, poor mechanical properties, and poor water resistance. Rainwater erosion will affect the dust suppression effect.
[0004] Based on the above statements, the present application provides an environmentally friendly dust suppressant for coal transportation and a preparation method thereof. Summary of the invention
[0005] In order to solve the technical problems that most dust suppressants in the prior art have poor mechanical properties and water resistance, and rain erosion can lead to a decrease in dust suppression effect, the present application provides an environmentally friendly dust suppressant for coal transportation and a preparation method thereof.
[0006] An environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36-44 parts of functional components, 6-8 parts of modified sodium alginate, 0.02-0.06 parts of initiator, 2-3 parts of phytic acid, 2.8-3.2 parts of genipin and 320-360 parts of deionized water;
[0007] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0008] Add functional components, modified sodium alginate and initiator into deionized water, stir evenly, heat to 68-74°C, stir and react for 4-6 hours. After the reaction, add phytic acid and genipin, continue stirring for 0.6-0.8 hours, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0009] In the above reaction process, genipin can act as a cross-linking agent to promote chemical cross-linking between the functional components and the amino groups on the modified sodium alginate, thereby improving the water resistance of the prepared environmentally friendly dust suppressant.
[0010] Preferably, the initiator is ammonium persulfate or potassium persulfate.
[0011] Preferably, the functional component is prepared by the following steps:
[0012] Step A1, under nitrogen protection, xanthan gum and deionized water are stirred evenly, added into sodium periodate aqueous solution, stirred for 2.5-3.5 hours in the dark at 45-55° C., after the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered and dried to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 4.5-6.5:60:80-100:3-4, and sodium periodate has the characteristic of selective oxidation, and can oxidize vicinal diols in xanthan gum into aldehyde groups;
[0013] Step A2, add modified xanthan gum to anhydrous ethanol, stir evenly, heat to 26-30°C, add functionalized silk fibroin, heat to reflux, stir and react for 2.8-3.4h, after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 3-5:60-70:1.4-1.8. In the above reaction process, anhydrous ethanol is used as solvent, and the aldehyde group on the modified xanthan gum undergoes Schiff condensation reaction with the amino group on the functionalized silk fibroin to obtain the functional component.
[0014] Preferably, the mass fraction of the sodium periodate aqueous solution is 24-30%.
[0015] Preferably, the functionalized silk fibroin is prepared by the following steps:
[0016] Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 90-100° C. for 1-1.4 hours, taking out, washing, drying, and then dissolving in a lithium bromide aqueous solution, stirring evenly, dialyzing, and freeze-drying to obtain silk fibroin, wherein the mass ratio of silk to sodium carbonate aqueous solution and lithium bromide aqueous solution is 1-2:100-160:600-800;
[0017] Step B2, adding silk fibroin and itaconic anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 80-84°C, stirring for reaction for 4.2-5.6h, dialyzing, and drying to obtain modified silk fibroin, wherein the mass ratio of silk fibroin, itaconic anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.4-0.6:32-36:0.02-0.04:0.6-0.8, in the above reaction process, with tetrabutylammonium bromide as a catalyst and triethylamine as an acid binding agent, the silk fibroin and itaconic anhydride undergo a ring-opening esterification reaction to obtain the modified silk fibroin;
[0018] Step B3, add modified silk fibroin and tris(hydroxymethylaminomethane) to anhydrous ethanol, heat to 45-55°C, stir evenly, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 8-12 hours, after the reaction is completed, cool to room temperature, rotary evaporate, wash, and dry to obtain functionalized silk fibroin, wherein the mass ratio of modified silk fibroin, tris(hydroxymethylaminomethane), anhydrous ethanol and p-toluenesulfonic acid is 2-4:1.2-1.6:16-20:0.04-0.06. In the above reaction process, N,N'-dicyclohexylcarbodiimide is used as a dehydrating agent and p-toluenesulfonic acid is used as a catalyst. The carboxyl group on the modified silk fibroin undergoes an esterification reaction with the hydroxyl group on the tris(hydroxymethylaminomethane) to obtain functionalized silk fibroin.
[0019] Preferably, in step B1, the pore size of the dialysis bag used in the dialysis process is 100-120 kDa, and the dialysis time is 42-48 h.
[0020] Preferably, in step B2, the pore size of the dialysis bag used in the dialysis process is 220-240 kDa, and the dialysis time is 12-18 hours.
[0021] Preferably, the mass fraction of the sodium carbonate aqueous solution is 12-16%.
[0022] Preferably, the mass fraction of the lithium bromide aqueous solution is 22-26%.
[0023] Preferably, the modified sodium alginate is prepared by the following steps:
[0024] Sodium alginate and deionized water are mixed, stirred evenly at room temperature, the pH value is adjusted to 8-9, and then a mixed solution of octenyl succinic anhydride and isopropanol is added dropwise, the temperature is kept constant, stirring is continued for 4-6 hours, the pH value is adjusted to 6.4-6.8, washed, and dried to obtain modified sodium alginate, wherein the mass ratio of sodium alginate, deionized water and the mixed solution is 6-8:100-120:20, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution is 2-4:90. In the above reaction process, deionized water is used as solvent and sodium hydroxide solution is used as alkaline catalyst, and sodium alginate and octenyl succinic anhydride undergo ring-opening esterification reaction to obtain modified sodium alginate solution.
[0025] In summary, this application has the following beneficial effects:
[0026] (1) In order to improve the wind erosion resistance, mechanical properties and water resistance of the environmentally friendly dust suppressant for coal transportation, the present application starts from two aspects. First, a functional component is added, and the functional component contains a xanthan gum structure, a Schiff base structure, a silk protein structure, an amino group and an ester group. The presence of the xanthan gum structure, on the one hand, can have good viscosity so that it can tightly bond the dust particles together to form a larger particle group, thereby effectively preventing the dust from flying and improving the wind erosion resistance of the environmentally friendly dust suppressant. On the other hand, it can chemically cross-link with phytic acid to improve the water resistance and mechanical properties of the environmentally friendly dust suppressant. The Schiff base structure is not only hydrophilic in itself, but also can form hydrogen bonds with the amino groups on the modified sodium alginate, further improving the water resistance and mechanical properties of the environmentally friendly dust suppressant. The presence of the silk protein structure, on the one hand, has the ability to adhere to and consolidate coal dust, thereby enhancing The added dust suppressant has a strong consolidation strength and improves the wind erosion resistance of the environmentally friendly dust suppressant. On the other hand, the amino group on it can chemically cross-link with the carboxyl group on the sodium alginate under the action of genipin, thereby improving the water resistance of the environmentally friendly dust suppressant. The presence of amino and ester groups can, on the one hand, improve the wind erosion resistance of the environmentally friendly dust suppressant. On the other hand, it can form hydrogen bonds with the active hydroxyl and carboxyl groups on the modified sodium alginate, further improving the water resistance of the dust suppressant. Secondly, the addition of modified sodium alginate can, on the one hand, exert the hydrophilicity of sodium alginate and thus improve the dust suppression of the dust suppressant. On the other hand, the octenylsuccinic anhydride grafted on the surface of the modified sodium alginate not only has a hydrophobic flexible chain structure, but also has a double bond that can produce chemical cross-linking with the functional components. Introducing it into the dust suppressant can synergize with the functional components to jointly improve the wind erosion resistance, water resistance and mechanical properties of the dust suppressant.
[0027] (2) The environmentally friendly dust suppressant for coal transportation prepared in the present application contains degradable structural units such as sodium alginate, xanthan gum, silk fibroin, ester group, and Schiff base structure, which can be degraded under mild conditions to achieve resource recycling and reuse, thus meeting the needs of sustainable social development. DETAILED DESCRIPTION
[0028] In order to make the implementation methods of the present application easier to understand, the present application will be described in detail below in conjunction with specific examples. These examples are only for illustration and are not limited to the scope of application of the present application.
[0029] The xanthan gum used in this application is produced by Aladdin Co., Ltd. and has a USP grade purity; the coal is specifically lignite produced by Shenmu Chuangyou Energy Technology Co., Ltd., with a calorific value of 6300, an ash content of 3%, a volatility of 30%, a content of 5.0%, a total sulfur of 0.21%, and a total water content of 9%; the sodium alginate is the Mingyue brand sodium alginate powder commercially available from Guangzhou Huayu Biotechnology Co., Ltd. Except for the raw materials mentioned above, the rest are commercially available.
[0030] Preparation Example 1-3 and Comparative Preparation Example 1-2 provide a functionalized silk fibroin.
[0031] Preparation Example 1
[0032] This preparation example provides a functionalized silk fibroin, which is prepared by the following steps:
[0033] Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 90°C and a rotation speed of 600 rpm for 1 hour, taking out, washing with deionized water for 3 times, drying at 55°C to constant weight, and then dissolving in a lithium bromide aqueous solution, stirring at a speed of 720 rpm for 18 minutes until uniform, the pore size is 100 kDa, the dialysis time is 42 hours, the freeze-drying temperature is -36°C, the vacuum degree is 13 Pa, and the drying time is 16 hours to obtain silk fibroin, wherein the mass ratio of silk, sodium carbonate aqueous solution and lithium bromide aqueous solution is 1:100:600, the mass fraction of sodium carbonate aqueous solution is 12%, and the mass fraction of lithium bromide aqueous solution is 22%;
[0034] Step B2, adding silk fibroin and itaconic anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 80°C, stirring for reaction for 4.2h, dialyzing through a dialysis bag with a pore size of 220kDa for 12h, freeze-drying at a temperature of -40°C, a vacuum degree of 11Pa, and a drying time of 24h to obtain modified silk fibroin, wherein the mass ratio of silk fibroin, itaconic anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.4:32:0.02:0.6;
[0035] Step B3, add modified silk fibroin and tris(hydroxymethyl)aminomethane) to anhydrous ethanol, heat to 45°C, stir at a speed of 720rpm for 14min until uniform, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 8h, after the reaction is completed, cool to room temperature, control the rotary evaporation temperature to 55°C, rotary evaporation to remove anhydrous ethanol, wash with deionized water 3 times, and dry at 60°C to constant weight to obtain functionalized silk fibroin, wherein the mass ratio of modified silk fibroin, tris(hydroxymethyl)aminomethane, anhydrous ethanol and p-toluenesulfonic acid is 2:1.2:16:0.04.
[0036] Preparation Example 2
[0037] This preparation example provides a functionalized silk fibroin, which is prepared by the following steps:
[0038] Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 95°C and a rotation speed of 700 rpm for 1.2 hours, taking out, washing with deionized water for 4 times, drying at 60°C to constant weight, and then dissolving in a lithium bromide aqueous solution, stirring at a speed of 740 rpm for 20 minutes until uniform, dialyzing for 45 hours through a pore size of 110 kDa, freeze-drying at a temperature of -34°C, a vacuum degree of 12 Pa, and a drying time of 14 hours to obtain silk fibroin; wherein the mass ratio of silk, sodium carbonate aqueous solution and lithium bromide aqueous solution is 1.5:130:700, the mass fraction of sodium carbonate aqueous solution is 14%, and the mass fraction of lithium bromide aqueous solution is 24%;
[0039] Step B2, adding silk fibroin and itaconic anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 82°C, stirring for reaction for 4.9h, dialyzing through a dialysis bag with a pore size of 230kDa for 15h, freeze-drying at a temperature of -36°C, a vacuum degree of 15Pa, and a drying time of 40h to obtain modified silk fibroin, wherein the mass ratio of silk fibroin, itaconic anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.5:34:0.03:0.7;
[0040] Step B3, add modified silk fibroin and tris(hydroxymethylaminomethane) to anhydrous ethanol, heat to 50°C, stir at a speed of 740rpm for 16min until uniform, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 10h, after the reaction is completed, cool to room temperature, control the rotary evaporation temperature to 60°C, rotary evaporation to remove anhydrous ethanol, wash with deionized water 4 times, and dry at 64°C to constant weight to obtain functionalized silk fibroin, wherein the mass ratio of modified silk fibroin, tris(hydroxymethylaminomethane), anhydrous ethanol and p-toluenesulfonic acid is 3:1.4:18:0.05.
[0041] Preparation Example 3
[0042] This preparation example provides a functionalized silk fibroin, which is prepared by the following steps:
[0043] Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 100°C and a rotation speed of 800 rpm for 1.4 hours, taking out, washing with deionized water for 5 times, drying at 65°C to constant weight, and then dissolving in a lithium bromide aqueous solution, stirring at a speed of 760 rpm for 22 minutes until uniform, dialyzing through a dialysis bag with a pore size of 240 kDa for 3.0 hours, freeze-drying at a temperature of -32°C, a vacuum degree of 15 Pa, and a drying time of 16 hours to obtain silk fibroin, wherein the mass ratio of silk, sodium carbonate aqueous solution and lithium bromide aqueous solution is 2:160:800, the mass fraction of sodium carbonate aqueous solution is 16%, and the mass fraction of lithium bromide aqueous solution is 26%;
[0044] Step B2, adding silk fibroin and itaconic anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 80°C, stirring for reaction for 5.6 hours, dialyzing through a dialysis bag with a pore size of 240 kDa for 18 hours, freeze-drying at a temperature of -34°C, a vacuum degree of 14 Pa, and a drying time of 36 hours to obtain modified silk fibroin, wherein the mass ratio of silk fibroin, itaconic anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.6:36:0.04:0.8;
[0045] Step B3, add modified silk fibroin and tris(hydroxymethyl)aminomethane) to anhydrous ethanol, heat to 55°C, stir at a speed of 760rpm for 18min until uniform, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 12h, after the reaction is completed, cool to room temperature, control the rotary evaporation temperature to 65°C, rotary evaporation to remove anhydrous ethanol, wash with deionized water 5 times, and dry at 68°C to constant weight to obtain functionalized silk fibroin, wherein the mass ratio of modified silk fibroin, tris(hydroxymethyl)aminomethane, anhydrous ethanol and p-toluenesulfonic acid is 4:1.6:20:0.06.
[0046] Comparative Preparation Example 1
[0047] This comparative preparation example provides a functionalized silk fibroin, which is prepared by the following steps:
[0048] Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 90°C and a rotation speed of 600 rpm for 1 hour, taking out, washing with deionized water for 3 times, drying at 55°C to constant weight, and then dissolving in a lithium bromide aqueous solution, stirring at a speed of 720 rpm for 18 minutes until uniform, the pore size is 100 kDa, the dialysis time is 42 hours, the freeze-drying temperature is -36°C, the vacuum degree is 13 Pa, and the drying time is 16 hours to obtain silk fibroin, wherein the mass ratio of silk, sodium carbonate aqueous solution and lithium bromide aqueous solution is 1:100:600, the mass fraction of sodium carbonate aqueous solution is 12%, and the mass fraction of lithium bromide aqueous solution is 22%;
[0049] Step B2, adding silk fibroin and butyric anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 80°C, stirring for reaction for 4.2h, dialyzing through a dialysis bag with a pore size of 220kDa for 12h, freeze-drying at a temperature of -40°C, a vacuum degree of 11Pa, and a drying time of 24h to obtain modified silk fibroin, wherein the mass ratio of silk fibroin, butyric anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.4:32:0.02:0.6;
[0050] Step B3, add modified silk fibroin and tris(hydroxymethyl)aminomethane) to anhydrous ethanol, heat to 45°C, stir at a speed of 720rpm for 14min until uniform, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 8h, after the reaction is completed, cool to room temperature, control the rotary evaporation temperature to 55°C, rotary evaporation to remove anhydrous ethanol, wash with deionized water 3 times, and dry at 60°C to constant weight to obtain functionalized silk fibroin, wherein the mass ratio of modified silk fibroin, tris(hydroxymethyl)aminomethane, anhydrous ethanol and p-toluenesulfonic acid is 2:1.2:16:0.04.
[0051] Comparative Preparation Example 2
[0052] This comparative preparation example provides a functionalized silk fibroin, which is prepared by the following steps:
[0053] Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 90°C and a rotation speed of 600 rpm for 1 hour, taking out, washing with deionized water for 3 times, drying at 55°C to constant weight, and then dissolving in a lithium bromide aqueous solution, stirring at a speed of 720 rpm for 18 minutes until uniform, the pore size is 100 kDa, the dialysis time is 42 hours, the freeze-drying temperature is -36°C, the vacuum degree is 13 Pa, and the drying time is 16 hours to obtain silk fibroin, wherein the mass ratio of silk, sodium carbonate aqueous solution and lithium bromide aqueous solution is 1:100:600, the mass fraction of sodium carbonate aqueous solution is 12%, and the mass fraction of lithium bromide aqueous solution is 22%;
[0054] Step B2, adding silk fibroin and itaconic anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 80°C, stirring for reaction for 4.2h, dialyzing through a dialysis bag with a pore size of 220kDa for 12h, freeze-drying at a temperature of -40°C, a vacuum degree of 11Pa, and a drying time of 24h to obtain modified silk fibroin, wherein the mass ratio of silk fibroin, itaconic anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.4:32:0.02:0.6;
[0055] Step B3, add modified silk fibroin and ethanolamine to anhydrous ethanol, heat to 45°C, stir at a speed of 720 rpm for 14 minutes until uniform, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 8 hours, after the reaction is completed, cool to room temperature, control the rotary evaporation temperature to 55°C, rotary evaporation to remove anhydrous ethanol, wash with deionized water 3 times, and dry at 60°C to constant weight to obtain functionalized silk fibroin, wherein the mass ratio of modified silk fibroin, ethanolamine, anhydrous ethanol and p-toluenesulfonic acid is 2:1.2:16:0.04.
[0056] Preparation Examples 4-6 and Comparative Preparation Examples 3-5 provide a functional component.
[0057] Preparation Example 4
[0058] This preparation example provides a functional component, which is prepared by the following steps:
[0059] Step A1, under nitrogen protection, xanthan gum and deionized water are stirred at a speed of 560 rpm for 16 minutes until uniform, added into a sodium periodate aqueous solution, kept at a temperature of 45°C in the dark and kept at a constant speed, and stirred for 2.5 hours. After the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered, and dried at 54°C to constant weight to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 4.5:60:80:3, and the mass fraction of sodium periodate aqueous solution is 24%;
[0060] Step A2, add modified xanthan gum to anhydrous ethanol, stir at a speed of 600 rpm for 14 minutes until uniform, heat to 26°C, add the functionalized silk fibroin prepared in Preparation Example 1, heat to reflux, maintain the speed unchanged, continue stirring to react for 2.8 hours, after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 3:60:1.4.
[0061] Preparation Example 5
[0062] This preparation example provides a functional component, which is prepared by the following steps:
[0063] Step A1, under nitrogen protection, xanthan gum and deionized water are stirred at a speed of 600 rpm for 18 minutes until uniform, added into a sodium periodate aqueous solution, kept at a temperature of 50°C in the dark and kept at a constant speed, and stirred for 3.0 hours. After the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered, and dried at 56°C to constant weight to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 5.5:60:90:3.5, and the mass fraction of sodium periodate aqueous solution is 27%;
[0064] Step A2, add modified xanthan gum to anhydrous ethanol, stir at a speed of 640 rpm for 16 minutes until uniform, heat to 28°C, add the functionalized silk fibroin prepared in Preparation Example 2, heat to reflux, maintain the speed unchanged, continue stirring to react for 3.1 hours, after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 4:65:1.6.
[0065] Preparation Example 6
[0066] This preparation example provides a functional component, which is prepared by the following steps:
[0067] Step A1, under nitrogen protection, xanthan gum and deionized water are stirred at a speed of 640 rpm for 20 minutes until uniform, added into a sodium periodate aqueous solution, kept at a temperature of 55°C in the dark and kept at a constant speed, and stirred for 3.5 hours. After the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered, and dried at 58°C to constant weight to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 6.5:60:100:4, and the mass fraction of sodium periodate aqueous solution is 30%;
[0068] Step A2, add modified xanthan gum to anhydrous ethanol, stir at a speed of 680 rpm for 18 minutes until uniform, heat to 30°C, add the functionalized silk fibroin prepared in Preparation Example 3, heat to reflux, maintain the speed unchanged, continue stirring to react for 3.4 hours, and after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 5:70:1.8.
[0069] Comparative Preparation Example 3
[0070] This comparative preparation example provides a functional component, which is prepared by the following steps:
[0071] Step A1, under nitrogen protection, xanthan gum and deionized water are stirred at a speed of 560 rpm for 16 minutes until uniform, added into a sodium periodate aqueous solution, kept at a temperature of 45°C in the dark and kept at a constant speed, and stirred for 2.5 hours. After the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered, and dried at 54°C to constant weight to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 4.5:60:80:3, and the mass fraction of sodium periodate aqueous solution is 24%;
[0072] Step A2, add modified xanthan gum to anhydrous ethanol, stir at a speed of 600 rpm for 14 minutes until uniform, heat to 26°C, add the functionalized silk fibroin prepared in Comparative Preparation Example 1, heat to reflux, maintain the speed unchanged, continue stirring to react for 2.8 hours, and after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 3:60:1.4.
[0073] Comparative Preparation Example 4
[0074] This comparative preparation example provides a functional component, which is prepared by the following steps:
[0075] Step A1, under nitrogen protection, xanthan gum and deionized water are stirred at a speed of 560 rpm for 16 minutes until uniform, added into a sodium periodate aqueous solution, kept at a temperature of 45°C in the dark and kept at a constant speed, and stirred for 2.5 hours. After the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered, and dried at 54°C to constant weight to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 4.5:60:80:3, and the mass fraction of sodium periodate aqueous solution is 24%;
[0076] Step A2, add modified xanthan gum to anhydrous ethanol, stir at a speed of 600 rpm for 14 minutes until uniform, heat to 26°C, add the functionalized silk fibroin prepared in Comparative Preparation Example 2, heat to reflux, maintain the speed unchanged, continue stirring to react for 2.8 hours, and after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 3:60:1.4.
[0077] Comparative Preparation Example 5
[0078] This comparative preparation example provides a functional component, which is prepared by the following steps:
[0079] Step A1, under nitrogen protection, stirring xanthan gum and deionized water at a rotation speed of 560 rpm for 16 minutes until uniform, adding to ethanol aqueous solution, maintaining the rotation speed unchanged at a temperature of 45°C in the dark, and continuing stirring for 2.5 hours. After the reaction is completed, adding ethylene glycol to terminate the reaction, standing and filtering, using acetone to precipitate, filtering, and drying at 54°C to constant weight to obtain modified xanthan gum, wherein the mass ratio of xanthan gum, deionized water, ethanol aqueous solution and ethylene glycol is 4.5:60:80:3, and the mass fraction of ethanol aqueous solution is 24%;
[0080] Step A2, add modified xanthan gum to anhydrous ethanol, stir at a speed of 600 rpm for 14 minutes until uniform, heat to 26°C, add the functionalized silk fibroin prepared in Preparation Example 1, heat to reflux, maintain the speed unchanged, continue stirring to react for 2.8 hours, after the reaction is completed, reduce pressure and concentrate to obtain functional components, wherein the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 3:60:1.4.
[0081] Preparation Examples 7-9 and Comparative Preparation Example 6 provide a modified sodium alginate.
[0082] Preparation Example 7
[0083] This preparation example provides a modified sodium alginate, which is prepared by the following steps:
[0084] Sodium alginate and deionized water were mixed, stirred at room temperature at a rotation speed of 640 rpm for 12 minutes until uniform, the pH value was adjusted to 8 with a 0.8M sodium hydroxide aqueous solution, and then a mixed solution of octenyl succinic anhydride and isopropanol was added dropwise, the temperature was kept constant, and stirring was continued for 4 hours. The pH value was adjusted to 6.4 with a 0.6M hydrochloric acid aqueous solution, washed with deionized water for 3 times, and dried at 56°C to constant weight to obtain modified sodium alginate, wherein the mass ratio of sodium alginate, deionized water and the mixed solution was 6:100:20, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution was 2:90.
[0085] Preparation Example 8
[0086] This preparation example provides a modified sodium alginate, which is prepared by the following steps:
[0087] Sodium alginate and deionized water were mixed, stirred at room temperature at a rotation speed of 660 rpm for 16 minutes until uniform, the pH value was adjusted to 8.5 with a 1.0 M sodium hydroxide aqueous solution, and then a mixed solution of octenyl succinic anhydride and isopropanol was added dropwise, the temperature and the rotation speed were kept constant, and stirring was continued for 5 hours. The pH value was adjusted to 6.6 with a 0.8 M hydrochloric acid aqueous solution, and the mixture was washed with deionized water for 4 times and dried at 60° C. to constant weight to obtain modified sodium alginate, wherein the mass ratio of sodium alginate, deionized water and the mixed solution was 7:110:20, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution was 3:90.
[0088] Preparation Example 9
[0089] This preparation example provides a modified sodium alginate, which is prepared by the following steps:
[0090] Sodium alginate and deionized water were mixed, stirred at room temperature at a speed of 700 rpm for 20 min until uniform, the pH value was adjusted to 9 with a 1.2 M sodium hydroxide aqueous solution, and then a mixed solution of octenyl succinic anhydride and isopropanol was added dropwise, the temperature was kept constant, and stirring was continued for 6 h. The pH value was adjusted to 6.8 with a 1.0 M hydrochloric acid aqueous solution, washed with deionized water for 5 times, and dried at 64° C. to constant weight to obtain modified sodium alginate, wherein the mass ratio of sodium alginate, deionized water and the mixed solution was 8:120:20, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution was 4:90.
[0091] Comparative Preparation Example 6
[0092] This comparative preparation example provides a modified sodium alginate, which is prepared by the following steps:
[0093] Sodium alginate and deionized water were mixed, stirred at room temperature at a rotation speed of 640 rpm for 12 minutes until uniform, the pH value was adjusted to 8 with a 0.8M sodium hydroxide aqueous solution, and then a mixed solution of n-octylsuccinic anhydride and isopropanol was added dropwise, the temperature was kept constant, and stirring was continued for 4 hours. The pH value was adjusted to 6.4 with a 0.6M hydrochloric acid aqueous solution, washed with deionized water for 3 times, and dried at 56°C to constant weight to obtain modified sodium alginate, wherein the mass ratio of sodium alginate, deionized water and the mixed solution was 6:100:20, and the mass ratio of n-octylsuccinic anhydride and isopropanol in the mixed solution was 2:90.
[0094] Examples 1-3 and Comparative Examples 1-5 provide an environmentally friendly dust suppressant for coal transportation.
[0095] Example 1
[0096] This embodiment provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36 parts of the functional component prepared in Preparation Example 4, 6 parts of the modified sodium alginate prepared in Preparation Example 7, 0.02 parts of ammonium persulfate, 2 parts of phytic acid, 2.8 parts of genipin, and 320 parts of deionized water;
[0097] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0098] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at 550 rpm for 16 min until uniform, heat to 68 ° C, stir and react for 4 h. After the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.6 h, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0099] Example 2
[0100] This embodiment provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 40 parts of the functional component prepared in Preparation Example 5, 7 parts of the modified sodium alginate prepared in Preparation Example 8, 0.04 parts of potassium persulfate, 2.5 parts of phytic acid, 3.0 parts of genipin and 340 parts of deionized water;
[0101] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0102] Add functional components, modified sodium alginate and potassium persulfate into deionized water, stir at a speed of 570 rpm for 18 min until uniform, heat to 71°C, continue stirring for 5 h, and after the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.7 h, control the rotary evaporation temperature to 64°C, rotary evaporation to remove deionized water, and dry at 70°C to constant weight to obtain an environmentally friendly dust suppressant for coal transportation.
[0103] Example 3
[0104] This embodiment provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 44 parts of the functional component prepared in Preparation Example 6, 8 parts of the modified sodium alginate prepared in Preparation Example 9, 0.06 parts of ammonium persulfate, 3 parts of phytic acid, 3.2 parts of genipin, and 360 parts of deionized water;
[0105] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0106] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at a speed of 590 rpm for 20 min until uniform, heat to 74 ° C, continue stirring for 6 h, after the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.8 h, control the rotary evaporation temperature to 68 ° C, rotary evaporation to remove deionized water, dry at 72 ° C to constant weight, and obtain an environmentally friendly dust suppressant for coal transportation.
[0107] Comparative Example 1
[0108] This comparative example provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36 parts of the functional component prepared in comparative preparation example 3, 6 parts of modified sodium alginate prepared in preparation example 7, 0.02 parts of ammonium persulfate, 2 parts of phytic acid, 2.8 parts of genipin and 320 parts of deionized water;
[0109] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0110] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at 550 rpm for 16 min until uniform, heat to 68 ° C, stir and react for 4 h. After the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.6 h, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0111] Comparative Example 2
[0112] This comparative example provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36 parts of the functional component prepared in comparative preparation example 4, 6 parts of modified sodium alginate prepared in preparation example 7, 0.02 parts of ammonium persulfate, 2 parts of phytic acid, 2.8 parts of genipin and 320 parts of deionized water;
[0113] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0114] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at 550 rpm for 16 min until uniform, heat to 68 ° C, stir and react for 4 h. After the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.6 h, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0115] Comparative Example 3
[0116] This comparative example provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36 parts of the functional component prepared in comparative preparation example 5, 6 parts of modified sodium alginate prepared in preparation example 7, 0.02 parts of ammonium persulfate, 2 parts of phytic acid, 2.8 parts of genipin and 320 parts of deionized water;
[0117] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0118] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at 550 rpm for 16 min until uniform, heat to 68 ° C, stir and react for 4 h. After the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.6 h, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0119] Comparative Example 4
[0120] This comparative example provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36 parts of the functional component prepared in Preparation Example 4, 6 parts of the modified sodium alginate prepared in Comparative Preparation Example 6, 0.02 parts of ammonium persulfate, 2 parts of phytic acid, 2.8 parts of genipin and 320 parts of deionized water;
[0121] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0122] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at 550 rpm for 16 min until uniform, heat to 68 ° C, stir and react for 4 h. After the reaction, add phytic acid and genipin, maintain the speed unchanged, continue stirring for 0.6 h, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0123] Comparative Example 5
[0124] This comparative example provides an environmentally friendly dust suppressant for coal transportation, comprising the following raw materials in parts by weight: 36 parts of the functional component prepared in Preparation Example 4, 6 parts of the modified sodium alginate prepared in Preparation Example 7, 0.02 parts of ammonium persulfate, 2 parts of propionic acid, 2.8 parts of genipin and 320 parts of deionized water;
[0125] The method for preparing the environmentally friendly dust suppressant for coal transportation comprises the following steps:
[0126] Add functional components, modified sodium alginate and ammonium persulfate into deionized water, stir at 550 rpm for 16 min until uniform, heat to 68 ° C, stir and react for 4 h. After the reaction, add propionic acid and genipin, maintain the speed unchanged, continue stirring for 0.6 h, rotary evaporate and dry to obtain an environmentally friendly dust suppressant for coal transportation.
[0127] Performance Testing
[0128] 20g of lignite was added to 8 containers in turn, and 0.8g of the environmentally friendly dust suppressant for coal transportation prepared in Examples 1-3 and Comparative Examples 1-5 and 10mL of water were evenly sprayed to obtain a mixed solution a, and the mixture was placed outdoors to dry and solidify naturally to form a film. A hair dryer was used to simulate natural wind for testing. The wind speed was changed by adjusting the distance between the air outlet and the coal powder. The wind speed value was measured by an anemometer. The wind speed was set to 15m / s and the duration was 1h. The mass loss rate (R,%) of the coal powder was calculated using formula (1);
[0129] (1)
[0130] In the formula, B1 and B 2 Respectively represent the mass of coal powder before and after wind blowing, the specific data are shown in Table 1 below;
[0131] Referring to GB / T1040.3-2006, the film was cut into a 10mm×100mm rectangle and its tensile strength and elongation at break were tested using a universal material testing machine. The test speed was 100mm / min and the initial clamping distance was 50mm. Each group of films was tested three times. The samples were sprayed with a water spray intensity of 100mL / 12h (heavy rain level) for 80 minutes. After that, they were placed outdoors and their tensile strength was measured after drying. The water resistance effect was evaluated by the change in its tensile strength. The surface hardness of the coal powder shell (thickness <6mm) was tested using a Shore hardness tester. The measurements were performed three times and the results were averaged. The specific test results are shown in Table 1 below.
[0132] Degradability test
[0133] The environmentally friendly dust suppressant for coal transportation prepared in Examples 1-3 and Comparative Examples 1-5 was mixed with water to obtain a mixed solution b with a mass fraction of 5%, which was sprayed on a glass plate (thickness 2 mm), and the glass plate was placed in an oven and dried at 60°C to solidify the film. The dried solidified film (1 g) was buried in simulated natural soil (maximum particle size 300 g < 270 μm), stored at 25°C for 56 days, and taken out after each cycle (1 cycle 7 days), the surface debris was cleaned, and the film was weighed after drying, and then put back into the soil. The degradation rate of the solidified film in each cycle was calculated. The degradation rate (D, %) of the environmentally friendly dust suppressant for coal transportation prepared in Examples 1-3 and Comparative Examples 1-5 was calculated using formula (2):
[0134] (2)
[0135] Wherein, M1 is the original mass of the environmentally friendly dust suppressant for coal transportation prepared in Examples 1-3 and Comparative Examples 1-5, g; M2 is the mass after degradation, g.
[0136] Table 1 Wind erosion resistance, mechanical properties, water resistance and degradation test of dust suppressants prepared in Examples 1-3 and Comparative Examples 1-5
[0137]
[0138] It can be seen from Table 1 that, compared with Comparative Examples 1-5, the environmentally friendly dust suppressant for coal transportation prepared in Examples 1-3 has more excellent wind erosion resistance, mechanical properties, water resistance and degradation properties.
[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly dust suppressant for coal transportation, characterized in that: The invention comprises the following raw materials in parts by weight: 36-44 parts of functional components, 6-8 parts of modified sodium alginate, 0.02-0.06 parts of initiator, 2-3 parts of phytic acid, 2.8-3.2 parts of genipin and 320-360 parts of deionized water; The functional component is firstly prepared by selectively oxidizing xanthan gum with sodium periodate to obtain modified xanthan gum, and then reacting the xanthan gum with functionalized silk fibroin through Schiff condensation reaction; The functionalized silk fibroin is firstly treated with a sodium carbonate aqueous solution, then treated with a lithium bromide aqueous solution to obtain the silk fibroin, then subjected to a ring-opening esterification reaction with itaconic anhydride to obtain the modified silk fibroin, and finally subjected to an esterification reaction with tris(hydroxymethyl)aminomethane to obtain the functionalized silk fibroin; The modified sodium alginate is prepared by a ring-opening esterification reaction of sodium alginate and octenyl succinic anhydride.
2. An environmentally friendly dust suppressant for coal transportation according to claim 1, characterized in that: The functional component is prepared by the following steps: Step A1, under nitrogen protection, xanthan gum and deionized water are stirred evenly, added into a sodium periodate aqueous solution, stirred for 2.5-3.5 hours in a dark environment at a temperature of 45-55° C., after the reaction is completed, ethylene glycol is added to terminate the reaction, the mixture is allowed to stand and filtered, precipitated with acetone, filtered and dried to obtain modified xanthan gum; Step A2, add modified xanthan gum to anhydrous ethanol, stir evenly, heat to 26-30°C, add functionalized silk fibroin, heat to reflux, stir to react for 2.8-3.4h, and after the reaction is completed, concentrate under reduced pressure to obtain functional components.
3. An environmentally friendly dust suppressant for coal transportation according to claim 2, characterized in that: In the step A1, the mass ratio of xanthan gum, deionized water, sodium periodate aqueous solution and ethylene glycol is 4.5-6.5:60:80-100:3-4.
4. An environmentally friendly dust suppressant for coal transportation according to claim 2, characterized in that: In the step A2, the mass ratio of modified xanthan gum, anhydrous ethanol and functionalized silk fibroin is 3-5:60-70:1.4-1.
8.
5. An environmentally friendly dust suppressant for coal transportation according to claim 2, characterized in that: The functionalized silk fibroin is prepared by the following steps: Step B1, adding silk to a sodium carbonate aqueous solution, stirring at 90-100° C. for 1-1.4 hours, taking out, washing, drying, and then dissolving in a lithium bromide aqueous solution, stirring evenly, dialyzing, and freeze-drying to obtain silk fibroin; Step B2, adding silk fibroin and itaconic anhydride to a formic acid aqueous solution, then adding tetrabutylammonium bromide and triethylamine, heating to 80-84° C., stirring and reacting for 4.2-5.6 hours, dialyzing, and drying to obtain modified silk fibroin; Step B3, add modified silk fibroin and tris(hydroxymethyl)aminomethane into anhydrous ethanol, heat to 45-55°C, stir evenly, then add p-toluenesulfonic acid, heat to reflux, continue stirring to react for 8-12h, after the reaction is completed, cool to room temperature, rotary evaporate, wash, and dry to obtain functionalized silk fibroin.
6. An environmentally friendly dust suppressant for coal transportation according to claim 5, characterized in that: In the step B1, the mass ratio of silk, sodium carbonate aqueous solution and lithium bromide aqueous solution is 1-2:100-160:600-800, in the step B2, the mass ratio of silk fibroin, itaconic anhydride, formic acid aqueous solution, tetrabutylammonium bromide and triethylamine is 1:0.4-0.6:32-36:0.02-0.04:0.6-0.8, and in the step B3, the mass ratio of modified silk fibroin, tris(hydroxymethyl)aminomethane, anhydrous ethanol and p-toluenesulfonic acid is 2-4:1.2-1.6:16-20:0.04-0.
06.
7. The environmentally friendly dust suppressant for coal transportation according to claim 1, characterized in that: The modified sodium alginate is prepared by the following steps: Mix sodium alginate and deionized water, stir evenly at room temperature, adjust the pH value to 8-9, then drop a mixture of octenyl succinic anhydride and isopropanol, keep the temperature constant, continue stirring for 4-6 hours, adjust the pH value to 6.4-6.8, wash, and dry to obtain modified sodium alginate.
8. An environmentally friendly dust suppressant for coal transportation according to claim 7, characterized in that: The mass ratio of the sodium alginate, deionized water and the mixed solution is 6-8:100-120:
20. In the mixed solution, the mass ratio of octenyl succinic anhydride and isopropanol is 2-4:
90.
9. A method for preparing an environmentally friendly dust suppressant for coal transportation according to any one of claims 1 to 8, characterized in that: The following steps are involved: Functional components, modified sodium alginate and initiator are added into deionized water, stirred evenly, heated to 68-74°C, stirred and reacted for 4-6 hours. After the reaction, phytic acid and genipin are added, stirred for 0.6-0.8 hours, rotary evaporated and dried to obtain an environmentally friendly dust suppressant for coal transportation.
Citation Information
Patent Citations
Mining spraying dust-settling dust suppressant based on mussel chemistry, and preparation method thereof
CN113322049A
Preparation method of environment-friendly coal dust composite dust suppressant for spraying
CN113817446A
Conditioning composition for optimizing soil or sand surface conditions
US20240254393A1
Cited By
Preparation method of low-chlorine composite environment-friendly coal transportation anti-freezing agent
CN120737809A